Education law prevention for crime following and the impact of disabled against children - Marlina, Marlina; Mulyadi, Mahmud (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Children as the next generation of national and state struggles will determine the success and progress of the nation in the future. The rise of internet development and promiscuity through face books, wa, instructors raises the concern that children will be involved in the crime of sexual abuse. Protection and attention of parents, family and government for the development and future of children. Protection and legal policies as well as supervision and the social system of the community are very helpful in efforts to prevent the crime of sexual abuse and the effects of molestation on children. In partner villages, there are many parents, community leaders, traditional leaders and village officials who do not know the limits of criminal acts of sexual abuse and the effects of molestation on children's development in the future. In addition, the natural conditions of the partner villages are abundant with forests and hamlets as well as residents' houses within distance and level low education and income of citizens causes a lack of attention to the growth and development of children. The team considers it important to do legal education in partner villages. The method is with lectures, tutorials and distributing guidebooks to the community related to the theme of devotion. The results of the dedication show that there are 148 community cadres in partner villages who already have legal understanding and legal awareness about the factors that cause the crime of sexual abuse, the legal provisions for criminal acts of crime, criminological theories that cause delinquency and the impact on children and the collaboration of all components of society, parents, government villages and sub-districts in prevention efforts.